GENERAL PRINCIPLES OF LAW: Protective justice and the social order reproduction - Cambronero Torres, Andrei (2019)
This article sustains the thesis according to which the General Principles of Law (GPL or PGD according to its translation in Spanish), beyond a mere source of law, are a part of the instruments with which the Law has to carry out one of its recognized goals: justice – specifically, protective justice. From a general perspective, the hypothesis held in this paper will sustain, simultaneously, that such referents are instruments for the reproduction of a given social order.